IMPLEMENTASI KEBIJAKAN TENTANG PENERIMAAN PAJAK DAN BEA BALIK NAMA KENDARAAN BERMOTOR II PADA KANTOR UPTD (SAMSAT) DI KABUPATEN BULUNGAN - M. Ibnu Azhari R (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This article is an effort to describe about the implementation of tax policy majoring in vehicle. How does it contribute significantly to the local income especially in Kabupaten Bulungan. But there are several problems that faced by government in implementing this policy.